Experimental studies on the mechanical properties and deformation & failure mechanism of U-type confined concrete arch centering. (January 2016) - Wang, Q.; Jiang, B.; Li, S.C.; Wang, D.C.; Wang, F.Q.; Li, W.T.; Ren, Y.X.; Guo, N.B.; Shao, X.
Highlights: We propose U-type confined concrete arch centering (UCCAC) support system applicable to deep roadways. A real scale confined concrete arch centering mechanical testing system was developed. The deformation and failure mechanism of the UCCAC by conducting indoor tests and numerical experiments were analyzed. The application on site shows the UCCAC support system has a superb effect on the surrounding rock control. Abstract: To solve the support problems of high stress roadways in deep mines, we developed a new 3D U-type confined concrete support system from the conventional U-type steel arch centering. Its core is the U-type confined concrete (UCC) arch centering. With a real scale mechanical test system for the confined concrete arch centering in underground engineering and numerical calculation methods, we studied in depth on the mechanical properties and deformation & failure mechanism of UCC arch centering (UCCAC). The results of the study show the yielding load and the limit load of UCC29 arch centering is 1230 kN and 1310 kN respectively in even pressure loading conditions; and a slight difference between the laboratory test and the numerical simulation on these two is 8.86% and 12.5% respectively. The deformation form of the arch centering is "vault uplifting, legs introverting and the overall shape becomes oval"; and the largest deformation occurs between the middle of the legs and the arch centering springing. The deformation and failure mechanism of arch centering is the partial strength failure causes the entire arch centering to lose its stability. The application on site shows the UCCAC has a superb effect on the surrounding rock control; therefore, the UCCAC is a new effective support for the high stress roadways in deep mines.